A pilot project- Causes of hypersegmentation in neutrophils apart from existing causes - Gunjan Bhatia; Namita Goyal; Priyanka Parakh; Shuchi Goyal; Shelesh Kumar Swami; Nitesh Kumar Chauhan (Journal of Pathology of Nepal)
Background: Hypersegmented neutrophils are one of the earliest indicators of megaloblastic anemia rather than raised MCV. Hypersegmented neutrophils are also seen as a part of myeloproliferative and myelodysplastic syndromes. Uremia, hyperthermia, and many drugs are also known to produce neutrophilic hypersegmentation. Congenital condition which is autosomal dominant in inheritance is known to cause hereditary hypersegmentation. We aimed to evaluate causes of hypersegmentation in peripheral smear apart from already known causes.